SUMBERDAYA MANUSIA GURU SMP DALAM RANGKA PENINGKATAN MUTU PENDIDIKAN (HUMAN RESOURCES OF JUNIOR HIGH SCHOOL TEACHER FOR IMPROVING THE EDUCATION QUALITY) - Jonni Sitorus (Inovasi, 2017)
To improve school quality, the school is need human resources (HR) of teacher’s competence to support the implementation of the learning process. School needs teachers that have the standards of competence. The purpose of the study is to analyze the qualification of junior high school teachers as well as their competence. The study emphasizes the qualitative process conducted in July to September 2014. The population is all junior high school teacher at North Tapanuli District. The study took a total sample. The informants were: North Tapanuli Education Department, principals, and teachers. Data collection techniques by means of structured interviews and documentary studies. Data were analyzed with descriptive qualitative. The results showed that the academic qualifications of teachers who meet the requirements as desired by the Ministerial Regulation 16/2007, at least 1,137 people University Graduate (86.202%) of the 1,319 total number of teachers and as many as 182 people (13.798%) has not met the requirement. By some junior high school teachers in North Tapanuli District already have and apply competence in teaching and learning. Recommended to the Department of Education at North Tapanuli District to conduct education and training for teachers to improve their competence; allocate sufficient budget to increase the academic qualifications of teachers, especially teachers who have a bachelor. Keywords: education quality, North Tapanuli district, Junior High School, teacher human resource, teacher qualification